The effect of mild to moderate COVID-19 infection on the cardiorespiratory fitness of firefighters - D'Isabel, Susanne; Berny, Lauren M.; Frost, Alex; Thongphok, Chanhtel; Jack, Kepra; Chaudhry, Sundeep; Arena, Ross; Smith, Denise L. (Frontiers in Public Health, 2023)
Introduction An adequate level of cardiorespiratory fitness (CRF) is critical for firefighters to perform the strenuous and physiologically demanding work of firefighting safely and effectively. The coronavirus disease 2019 (COVID-19) has been shown to negatively impact CRF in both the acute phase and longer-term following infection. This study aimed to determine changes to the CRF of firefighters pre- to post-mild to moderate COVID-19 infection and to investigate the impact of days past COVID-19 infection on change in CRF. Methods CRF measures from cardiopulmonary exercise testing (CPET) at annual occupational health exams that occurred pre-COVID-19 infection in 2019 were obtained for firefighters from seven Arizona fire departments. Measures were compared to CPET evaluations from annual health exams the following year in a cohort of firefighters who self-reported mild to moderate illness following COVID-19 infection between exams. Results Among a cohort of 103 firefighters, mean age 40 ± 9 years, CRF [as measured by peak oxygen consumption (VO2)] declined by an average of 2.55 ml·kg−1·min−1 or 7.3% (d = −0.38, p < 0.001) following COVID-19 infection (mean time from COVID-19 infection to CPET was 110 ± 78 days). The number of days past COVID-19 infection showed a small, yet significant, relationship to peak VO2 (r = 0.250, p = 0.011). Estimated marginal effects indicated that when biological sex, age, and BMI are controlled for, predicted peak VO2 returned to pre-COVID-19 values 300 days after COVID-19 infection. Conclusion Peak VO2 (ml·kg−1·min−1) declined 7.3% among firefighters an average of 110 days past reporting mild to moderate COVID-19 infection. This decrease has implications for the operational readiness and safety of firefighters.